Family Welfare Empowerment: Processing of Halalan Toyyiban Spicy and Sour Crab Based on Local Potential as an Effort to Create Food Self-Reliance and Diversification - Arni Rizqiani Rusydi; S. Sumiaty; Nur Ulmy Mahmud (Manunggal Halim Jaya, 2022)
Considering the various arguments from the Qur'an, hadith, the opinions of scholars, and scientific research, reinforced by the principles of Usul Fiqh, the law on consuming crabs is halal. In Indonesia. In several areas in South Sulawesi, this business is carried out using a silvofishery system, which combines the cultivation of fishery commodities in the form of milkfish and crabs with the planting of mangroves. In recent years, this has become an alternative for pond farmers for their failure in tiger prawn cultivation. Thus, an educational program in the form of counseling aims to foster public interest in consuming crabs to maintain their health. Besides that, it can also increase their knowledge about the nutritional content possessed by crabs in maintaining health. This counseling is led directly by a team of volunteers with the appropriate educational background, namely public health nutrition. The training aims to increase the skills and interest of the community regarding processing in the form of a spicy and sour crab, which has economic and healthy selling value. This training is led by a team of servants who have mastered the material for processing crabs into spicy and sour ones.